Building InformationCommunication Competences in Students' Learning Activities - Xusinova Laylo (Genius Journals, 2023)
This article introduces the problem of formation of ICT competence of future teachers. It discusses the process of educational informatization which relates to the ability of all participants of educational process to use modern information and communication technologies. The paper deals with the pedagogical potential of ICT, pedagogical methods, ICT means, pedagogical capabilities of ICT
Keywords: ICT competence; students; future teachers